Legal Protection of Shareholders in the Sale and Purchase of Limited Liability Companies Engaged in the Business of Coal Mining - HELLANDA, Clara Vinky; SENASTRI, Ni Made Jaya; SETIASA, Made (Journal of Political And Legal Sovereignty, 2025)
Purpose:In the practice of the mining industry, the acquisition of ownership of mining assets is often done through an acquisition mechanism of a business entity that already has a Mining Business Licence (IUP). One of the commonly used methods is through the sale and purchase of a Limited Liability Company (PT) holding a coal IUP. Therefore, it is important to examine how the role of notaries in buying and selling Limited Liability Companies in businesses engaged in Coal mining and how legal protection of shareholders in the sale and purchase of PT in the field of Coal mining. The objectives of the research are general research objectives and specific research objectives.Methodology:This research is a type of normative legal research. The approach used in this research is a statutory approach and a conceptual approach. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materialsFindings: Based on the results of the research, it is known that notaries play an important role in the sale and purchase of PTs engaged in the coal mining business through the making of deeds. Authentic deeds made by notaries not only function as legally valid and strong written evidence, but also as instruments capable of minimising legal risks that may arise in the future. In addition, based on the results of the research, it is known that the legal protection of shareholders in the sale and purchase transaction of PT, especially those engaged in coal mining, consists of preventive and repressive protection.Implication This research has an impact on notaries to understand their role in buying and selling Limited Liability Companies in businesses engaged in Coal mining. In addition, it has an impact on shareholders to understand the legal protection that must be obtained in the sale and purchase transaction of PT in the field of Coal mining.